Analysis of The Application of Good Manufacturing Practice (GMP) in The Production Process of Butterfly Pea Flower Syrup (Clitoria Ternatea L.) at UMKM Bu Karno, Jember Regency - Nugroho, Fauzan; Retnowati, Naning (Politeknik Negeri Jember, 2024)
The implementation of the Good Manufacturing Practice (GMP) program is a key effort by the company to ensure a safe food system for consumers. This research aims to identify and analyze the aspects of GMP implementation at UMKM Bu Karno, following the standards set by the Regulation of the Minister of Industry of the Republic of Indonesia Number 75 of 2010. Additionally, it provides recommendations for improvements to meet GMP requirements and enhance the effectiveness of its implementation. The research employs a qualitative descriptive method. The population consists of UMKM Bu Karno, with samples taken from business owners and experts in relevant fields. Data identification and analysis were conducted through questionnaires filled out using a checklist, with data analyzed using Gap Analysis for each aspect of GMP implementation. The processed data revealed an average total percentage of 70.06%, indicating that the GMP program at UMKM Bu Karno requires further improvement to fulfill GMP standards and enhance its effectiveness. The company should also consider the provided improvement recommendations to elevate the quality of GMP program implementation.